2023
DOI: 10.12688/f1000research.140607.1
|View full text |Cite
|
Sign up to set email alerts
|

Enteric-coating film effect on the delayed drug release of pantoprazole gastro-resistant generic tablets

Mosab Arafat,
Molham Sakkal,
Mohammad F. Bostanudin
et al.

Abstract: Background: Enteric coating films in acidic labile tablets protect the drug molecule from the acidic environment of the stomach. However, variations in the excipients used in the coating formulation may affect their ability to provide adequate protection. This study is the first to investigate the potential effects of coating materials on the protective functionality of enteric coating films for pantoprazole (PNZ) generic tablets after their recall from the market. Methods: A comparative analysis was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Overall, the quality of the medication is influenced by several factors: the physicochemical properties of the active ingredient, the types and proportions of excipients used, and their grades. These properties significantly impact the final product’s quality, as evidenced by various studies [ 24 , 25 , 26 , 27 ]. For instance, one study found that the hydrate form of cefdinir released faster than its monohydrate form [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, the quality of the medication is influenced by several factors: the physicochemical properties of the active ingredient, the types and proportions of excipients used, and their grades. These properties significantly impact the final product’s quality, as evidenced by various studies [ 24 , 25 , 26 , 27 ]. For instance, one study found that the hydrate form of cefdinir released faster than its monohydrate form [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The integration of thermal and analytical techniques, complemented by in vitro assessments, forms a comprehensive approach for identifying compromised quality and functionality in CDDSs [ 26 , 32 , 33 , 34 , 35 , 36 ]. Essential techniques include differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), X-ray diffraction (XRD), and scanning electron microscopy (SEM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation